Presenting the mash-up progress at higher education and its basic functions - Rabiu Ibrahim,; Oxley, Alan (2011)
Today mash-ups have been accepted by many users and by many organizations. The development of mash-ups is everywhere, yet until now there has been insufficient research and development of mash-up applications for use in the Higher Education. In this work, we focus on mash-ups in the Higher Education: its potential, how to provide training for users, and how to assess its effectiveness in the dissemination of information. Mash-up architecture consists of three main components: first is the content?service provider, second is the provider of the editor used to create the mash-up, and lastly is the server that hosts it and the client to whom the mash-up results are presented.